Project Appraisal Methodology: Market Penetration Elements - Silverman, Barry G. (Management Science, 1983)
This paper describes a multiple competing technologies market penetration model which incorporates multiple attributes rather than strictly price into the market share allocation function. The model which is linear and deterministic was developed in response to the sponsor's request for a simplified technological forecasting procedure. Its principal features include (a) a static nominal market share function based on multi-attribute scaling and maximum market fractions and (b) an effective market share function dependent on market potential forecasts, nominal market share, and a penetration delay curve. The model offers significant spatial, sectoral, and temporal resolution and may readily incorporate professional judgment (it is best implemented in a buyer-behavior survey mode). A version of the model is applied to the advanced energy combustion technology market in support of a DOE budget preparation exercise. Three sets of participants—program advocates, independent review panel, and system integrators—interacted in a series of solutions, defenses, and re-solutions of the model which permitted professional judgment and expert opinion to be solicited and incorporated in a systematic fashion. Model results indicate zero to very little penetration for several of the proposed projects. Parametrics reveal that results are most sensitive to (a) moderate shifts in commercialization date, (b) small changes in market growth rates (for technological penetrating expansion markets only), and (c) shifts in static market share curve coefficients.